Comparative evaluation of stresses in tooth implant connected fixed partial denture by varying the implant design and position: A 3D finite element study - K V Pratheep; Abby Abraham; H Annapoorni; S Vigneshwaran (Wolters Kluwer Medknow Publications, 2013)
Aim: This study aims at evaluating stresses generated in a fixed tooth to implant connected fixed partial denture (FPD) by finite element method by varying implant design and position, in unilateral distal extension cases, i.e. for replacing mandibular 1 st and 2 nd molars. Materials and Methods: Four models were created, Model 1-A finite element model (FEA) model of a crestal implant-tooth connected metal ceramic FPD with pontic in 36 region. The 35 region simulated the second premolar. Model 2-A FEA model of a basal implant-tooth connected metal ceramic FPD. Model 3-A FEA model of a crestal implant in 36 region connected to tooth 35 and cantilevered posteriorly with pontic in 37 region, made of metal ceramic. Model 4-A FEA model of a basal implant in 36 region connected to tooth 35 and cantilevered posteriorly with pontic in 37 region, made of metal ceramic. A vertical force of 100N directed evenly on the nodes on the occlusal surface of each of the three crowns. The models displayed stress both numerically and by color coding. Results: On comparing models 1 and 2, the model 1 showed comparatively more stresses in crestal bone area of the implant. On comparing models 3 and 4, model 3 showed lesser von misses stress values. Conclusion: In case of tooth implant connected FPDs without any cantilevers, basal implants show better stress distribution when compared to crestal implants. In case of cantilever designs, crestal implant design showed lower stress values, but the difference in stresses were less.